Diseño del sistema de riego por goteo en 332 hectáreas bajo el cultivo de caña de azúcar para el Ingenio Pantaleón, en Escuintla, Guatemala - Carpio-Carpio, Carlos (Instituto Tecnológico de Costa Rica, 2017)
This document presents the irrigation design for sugar cane in the 332 ha of the Finca Puyumate in Escuintla, Guatemala. A computer programs were used to obtain the agrometeorological data, an irrigation sheet of 6 mm/day and a system flow of 272,72 m3/h- 100ha were determined. It was established that the irrigation is done in two pumps, each divided into 5 shifts. The hydraulic design that best adapts to the terrain conditions is presented. It was decided to use self-compensating drip tape with a distance between emitters of 0.40 m and a separation between drip lines of 1.8 m. The irrigation operation table was made for each month of the year and for each growing season of the crop. And finally, the economic and environmental analysis was carried out
Proyecto de Graduación (Licenciatura en Ingeniería Agrícola) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Agrícola, 2017.
Keywords: Evapotranspiración; Riego por goteo; Fincas agrícolas; Sistemas hidráulicos; Diseño; Análisis; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Area technology::Agricultural engineering